Reactor modeling and simulation of moving-bed catalytic reforming process; Chemical Engineering Journal; Vol. 176-177 - Gyngazova M. S.; Kravtsov А. V. Anatoly Vasilyevich; Ivanchina E. D. Emilia Dmitrievna; Korolenko M. V.; Chekantsev N. V. (2011, 2011)
Catalytic reforming of naphtha is one of the most important processes for high octane gasoline manufacture and aromatic hydrocarbons production. Mathematical modeling method can be used for optimization and prediction of operating parameters (octane number, reactors outlet temperature and yield) of the reforming process. In this paper the new approach for mathematical modeling of a continuous catalytic regenerative (CCR) reforming process is proposed. The approach is based on components aggregation into pseudo components according to their reactivity; creation and application of pseudo components reaction scheme; finding the dependence of the reactivity of the hydrocarbons from the same homological group on their octane numbers. The novelty of the presented mathematical model of a moving-bed catalytic reforming reactor is the account of the catalyst work instability, coking, activity and circulating factor of the catalyst. The reformate composition calculated with the proposed model agrees very well with experimental information